1982
DOI: 10.1111/j.1432-1033.1982.tb07074.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Function Relations between Fatty Acid Oxidation and the Mitochondrial Inner‐Membrane — Matrix Region

Abstract: Decreasing the osmolarity of the incubation media for rat liver mitochondria, by lowering the KCl or sucrose content, greatly increased the oxidation of palmitate, palmitoyl-CoA, palmitoyl-(-)-carnitine, octanoate and butyrate, but only slightly affected the oxidation of succinate, glutamate plus malate, and 3-hydroxybutyrate. Kinetic studies indicated that the increased rate of fatty acid oxidation commenced at the onset of incubation in the hypotonic media and remained relatively constant. This was accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 28 publications
3
10
1
Order By: Relevance
“…Such an effect could be mediated by NAD+/NADH pool turnover, so that a dual inhibition of both the NAD' and ETF-linked stages by hyperosmotic conditions would explain the pattern of intermediates detected, with the ETF-linked stage inhibited more than the NAD+-linked stage at high osmolalities. However, the data of Otto and Ontko (1982) are not in agreement with this hypothesis as they found that 3-hydroxybutyrate/acetoacetate ratios increased with decreasing osmolality, rather than remaining constant, as would be expected if the NAD+/ NADH ratios were constant. Sub-compartmentation of intramitochondrial NAD' (Sumegi and Srere, 1984;Fukushima et al, 1989) could explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Such an effect could be mediated by NAD+/NADH pool turnover, so that a dual inhibition of both the NAD' and ETF-linked stages by hyperosmotic conditions would explain the pattern of intermediates detected, with the ETF-linked stage inhibited more than the NAD+-linked stage at high osmolalities. However, the data of Otto and Ontko (1982) are not in agreement with this hypothesis as they found that 3-hydroxybutyrate/acetoacetate ratios increased with decreasing osmolality, rather than remaining constant, as would be expected if the NAD+/ NADH ratios were constant. Sub-compartmentation of intramitochondrial NAD' (Sumegi and Srere, 1984;Fukushima et al, 1989) could explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 54%
“…This steady 30% reduction and the subsequent turnover of the NAD'NADH pool via the activity of complex I is probably important for the control of P-oxidation under these conditions. (Osmundsen and Bremer, 1976), by the rates of ketogenesis (Otto and Ontko, 1982), and polarographically with hexadecanoyl-carnitine by Halestrap and Dunlop (1986).…”
Section: Nad' and Nadh Concentrations During A Pulse Of P-oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the assumption that the cloned, immortalized vim Ϫ fibroblasts are restricted in their metabolic capacities partially because of a slow turnover of mtDNA-encoded mitochondrial proteins, efficient usage of already existent mitochondrial metabolons should be a remedial measure for solving this problem. This might include, on the one hand, swelling of the inner membrane-matrix compartment, a process which, via anchorage of multienzyme complexes of ␤-oxidation to the inner membrane (Parker and Engel, 2000), specifically activates fatty acid oxidation with concomitant elevation of the mitochondrial energy state (Otto and Ontko, 1982). Fatty acids are not only excellent respiratory substrates feeding electrons into the mitochondrial energy-generating respiratory chain, but they also promote mitochondrial swelling (Schönfeld et al, 2000).…”
Section: Mouse Fibroblast Immortalization and Vimentin 699mentioning
confidence: 99%
“…For instance, in the presence of glucagon, mitochondrial respiratory rate, pyruvate metabolism and citrulline synthesis are stimulated [18]. When external osmolarity was decreased, fatty acid oxidation was stimulated while cytochromes were more reduced [19]. In conditions of matrix volume condensation, an inhibition of mitochondrial substrate oxidation has been observed and interpreted as a consequence of an osmotically sensitive diffusion of quinones through the mitochondrial membrane [20].…”
Section: Introductionmentioning
confidence: 99%